The role of job satisfaction and perceived organizational support in improving employee work ethic - Devy Sofyanty; Vera Agustina Yanti; Sri Arfani; Danny Ong (Journal of Economics and Business Letters, 2021)
This research aims to test and analyze empirically the influence of job satisfaction and perceived organizational support partially or simultaneously on employee work ethic. The research method used quantitative methods while the data collection techniques were carried out through questionnaires, interviews and observations. The sampling technique used in this research was purposive sampling technique. Subjects in this study amounted to 75 employees at the Ministry of Industry the Republic of Indonesia. The data analysis technique used is multiple linear regression analysis processed using Statistical Package for the Social Sciences (SPSS) software. Based on the research results, the findings are as follows: (1) collectively or simultaneously job satisfaction and perceived organizational support has a positive and significant effect on work ethic, (2) partially job satisfaction has a positive and significant effect on work ethic; (3) partially perceived organizational support has a positive and significant effect on work ethic. Thus, work ethic can be increased by increasing job satisfaction and perceived organizational support.